Community Participation in Effort to Mitigate Caused by Mount Kelud Eruption in Ngancar District, Kediri Regency - Andri Estining Sejati; Muhammad Hasan; Desi Nurul Hidayati (SPATIAL: Wahana Komunikasi dan Informasi Geografi, 2019)
Indonesia location is between four plates, there are: Eurasian, Indo-Australian, Philiphines, dan Pasicic. Subduction between plates make Indonesia disturbed a natural incident such as mountain eruption. One of disturbed mountain eruption disaster area is District Ngancar, Kediri Regency. This case because Ngancar location near Kelud slope. People participation for efforts mitigations is very important for reduced natural incident impact. The aim this paper to discuss form and level people participation in District Ngancar for efforts Kelud mountain eruption disaster mitigation. This research is survey with sample 100 from 5.340 head family. The data collected with interview and documentation, then analized by quantitative description with scoring and percentage. The research result showing that people in disaster disturbed zone I, II, and III get participation score each the amount of 1.425, 935, and 1.133. The participation action, include: elucidation disaster, organizing disaster preparedness, preparing self, making early warning system, and saving property.